A Comparative Assessment of Driving Behaviours at Three Sites - Marsden, G. R.; McDonald, M.; Brackstone, M. (European Journal of Transport and Infrastructure Research, 2003)
Many Intelligent Transport Systems (ITS) that are now under intensive investigation have been designed or assessed with a particular target consumer group in mind. In order for these (and many other) systems to be successfully used around the globe however, some appreciation will be necessary of how behaviours, and hence uses and impacts, may change between different sites and between different countries. This article reports on an instrumented vehicle study designed to assess differences in Motorway driving behaviour between three sites, one in the U.K., one in France and one in Germany. Substantial differences were found between typical car-following headways and time to collisions observed at the sites. The experiment also confirmed that many people drive well below the current recommended safe following distances. It has not been possible through this study to determine why the differences exist between the sites, nor whether they are country specific. However, the findings are important in establishing that significant differences do exist. These differences could impact on the effectiveness of roadside telematics systems as well as for the design of in-vehicle Advanced Vehicle Control and Safety Systems.